Atlas of Implant Dentistry and Tooth-Preserving Surgery : Prevention and Management of Complications - Stajčić, Zoran (Springer International Publishing : Imprint: Springer, 2017)
This atlas is unique in comparing the two disciplines of dental implant surgery and tooth-preserving surgery with respect to common procedures, problems, and failures and in providing excellent guidance on the prevention and management of complications. The etiology of a wide variety of implant-related and non-implant-related complications and failures is carefully explained. Since many complications have their roots in oral and periodontal surgical maneuvers, these maneuvers are themselves discussed and extensively illustrated. The most frequently used tooth preservation procedures are also fully described, with emphasis on correct surgical technique as a means to avoid complications. The use of these procedures is constantly weighed against the effects of tooth removal and insertion of dental implants. The text is complemented by the inclusion of a substantial number of helpful references. While the atlas is intended primarily for dentists involved in outpatient implant dentistry and oral surgery, oral and maxillofacial surgeons will also find the descriptions of innovative techniques or maneuvers to be of interest, including those relating to the selection of incision and flap design and the sinus floor elevation techniques.
Keywords: Dentistry.; Oral surgery.; Maxillofacial surgery.; elektronické knihy; electronic books